Beyond Transformative Learning: Work, Ethical Space and Adult Education - Elizabeth Lange (Adult Education Research Conference, 2000)
This study concludes that transformative learning must be dialectically related to restorative learning given the progressive loss of ethical efficacy in the workplace and loss of organic connections to time, space, body and human relations.